2023
DOI: 10.1177/09544062231195472
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of turning process parameters using a new hybrid evolutionary algorithm

Hammoudi Abderazek,
Aissa Laouissi,
Mourad Nouioua
et al.

Abstract: In this article, a new hybrid improved differential evolution and Nelder-Mead (IDE-NM) is introduced for optimizing the multi-objective machining process during the turning operation under three modes of lubrication conditions. The fitness functions are the tangential cutting force, the surface roughness, and the cutting power. Five mixed design variables are considered in the optimization procedure including the cutting speed, feed rate, and depth of cut, mode of lubrication, and the type of cutting material.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Advanced mathematical optimization methods are analyzed and researched by solving a series of multiparametric optimization for real engineering problems. [5][6][7] In Abderazek et al, 5 a new hybrid optimization algorithm (improved differential evolution and Nelder-Mead -IDE-NM) is introduced for optimizing the multi-objective machining process during the turning operation under three modes of lubrication conditions. Five mixed design variables are considered in the optimization procedure, including the cutting speed, feed rate, depth of cut, mode of lubrication, and type of cutting material.…”
Section: Special Issue: Advanced Mathematical Modeling In Mechanical ...mentioning
confidence: 99%
“…Advanced mathematical optimization methods are analyzed and researched by solving a series of multiparametric optimization for real engineering problems. [5][6][7] In Abderazek et al, 5 a new hybrid optimization algorithm (improved differential evolution and Nelder-Mead -IDE-NM) is introduced for optimizing the multi-objective machining process during the turning operation under three modes of lubrication conditions. Five mixed design variables are considered in the optimization procedure, including the cutting speed, feed rate, depth of cut, mode of lubrication, and type of cutting material.…”
Section: Special Issue: Advanced Mathematical Modeling In Mechanical ...mentioning
confidence: 99%
“…The findings indicated that the highest material removal rate of 4550 mm 3 /min was achieved with a cutting speed of 100 m/min, a feed rate of 0.091 mm/rev, and a depth of cut of 0.4mm. Abderazek et al (2024) introduced an innovative multi-objective optimization algorithm termed Improved Differential Evolution and Nelder-Mead (IDE-NM). Their study incorporated three lubrication conditions and five key process parameters: cutting speed, feed rate, depth of cut, lubrication mode, and cutting material type.…”
Section: Ntukidem B I; Achebo J I; Ozigagun A; Uwoghiren F O; Obahiag...mentioning
confidence: 99%